Determinan Peringkat Obligasi pada Perusahaan Non Keuangan yang Terdaftar di BEI - Veliana, Susanto Salim (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to find out empirically whether corporate governance, profitability, leverage, and liquidity have an influence on bond ratings on non-financial companies that issue bonds and are listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The corporate governance proxies used are the size of the board of commissioners, independent commissioners, and audit committees. The data is used in the form of secondary data. The sample of this study was 78 data selected using non-probability sampling method and purposive sampling technique. This study was processed using the IBM Statistics SPSS version 28 program using ordinal logistic regression analysis. The results of this study indicate that board size, audit committee, and profitability have a significant positive effect on bond ratings. Leverage has a significant negative effect on bond ratings. Board independence and liquidity do not have a significant effect on bond ratings.